Genetic Predictors of Lithium Response - U. Heilbronner (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2019)
Lithium remains a first-line pharmacological treatment of bipolar disorder (BD). However, treatment response is heterogeneous, with several lines of evidence implicating genetic factors. Unfortunately, neither hypothesis-driven approaches nor initial genome-wide association studies (GWAS) were successful in identifying genetic drivers of response heterogeneity, probably due to low statistical power and different phenotype measurements. Recently, a GWAS of the Consortium of Lithium Genetics (ConLiGen) has identified four single nucleotide polymorphisms (SNPs) mediating response to lithium, located in genes for two long non-coding RNAs. This success was only possible by international collaboration and the use of an established lithium response scale. The findings await further replication.